2020
DOI: 10.1002/cre2.347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of life and satisfaction in patients using complete dentures versus mandibular overdentures. Systematic review and meta‐analysis

Abstract: Background The World Health Organization (WHO) recognizes edentulism as a physical impairment that results in a negative impact in the daily activities. Objective The study aimed to compare the satisfaction and the quality of life, in patients treated with implant retained overdentures with two mandibular implants (IOD) against those with mandibular conventional complete dentures (CCD). Methods Different search strategies were used to screen for articles in Pubmed/Medline, Cochrane Library and Scielo of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…5,8 Evaluation of the Third National Health and Nutrition Examination Survey (NHANES III) prosthodontic data found that approximately 60% of conventional denture users have at least one problem with their conventional denture 9 such as pain, chewing difficulties, speech alterations, and nutrition deficits. 3,4,[10][11][12] Due to these numerous, negative patient-based outcomes, other treatment modalities have been proposed to improve the stability and retention of a prosthesis, such as implant-retained overdenture. There is strong evidence that oral health-related quality of life measures are significantly improved with mandibular two-implant overdentures.…”
Section: Abstract Implant Angulation Overdenture Attachment Systems P...mentioning
confidence: 99%
See 3 more Smart Citations
“…5,8 Evaluation of the Third National Health and Nutrition Examination Survey (NHANES III) prosthodontic data found that approximately 60% of conventional denture users have at least one problem with their conventional denture 9 such as pain, chewing difficulties, speech alterations, and nutrition deficits. 3,4,[10][11][12] Due to these numerous, negative patient-based outcomes, other treatment modalities have been proposed to improve the stability and retention of a prosthesis, such as implant-retained overdenture. There is strong evidence that oral health-related quality of life measures are significantly improved with mandibular two-implant overdentures.…”
Section: Abstract Implant Angulation Overdenture Attachment Systems P...mentioning
confidence: 99%
“…There is strong evidence that oral health-related quality of life measures are significantly improved with mandibular two-implant overdentures. 4,[10][11][12][13][14][15] and that even the placement of a single implant may positively affect patient-based outcome measures. [16][17][18] These patients have an increase in social and sexual activity, 19 improved esthetics, speech, and stability of their prostheses.…”
Section: Abstract Implant Angulation Overdenture Attachment Systems P...mentioning
confidence: 99%
See 2 more Smart Citations
“…10 Several attempts have been made to detect patients' satisfaction with different types of prosthesis, confirming the best performance of fixed denture, compared to the other options. 6,11 Nevertheless, in addition to the purely clinical aspect, economic considerations are important for the choice of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%